Title Legal Principles of Contracts in Employment Contracts for Indonesian Migrant Workers Abroad - Surya, Ida (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The legal principles of agreements in employment agreements for Indonesian migrant workers (TKI) abroad aim to determine the application of legal principles of agreements in the placement of Indonesian migrant workers (PMI) abroad, and entering into employment agreements with people we do not know as well as the factors that cause violations of employment agreements for the placement of TKI abroad. This research is normative research, namely legal research conducted by examining library materials or in other words using secondary data, namely laws and regulations, Ministerial decisions, legal theories and expert opinions. The results of the research on the application of legal principles of agreements in the placement of Indonesian migrant workers (PMI) abroad have not been implemented properly. Coercion, fraud and abuse of circumstances occur in the placement of PMI abroad caused by the economic, social, educational or psychological conditions of the prospective PMI in the employment agreement which results in the service user in this case through the PMI placement company being more dominant in determining the terms and conditions of the employment agreement. This kind of agreement is known as Adhesie Contracten. This agreement condition is possible considering that the Civil Code does not adhere to the principle of Justuta Pretitum, so there are no requirements that require the creation of a balance between the achievements of both parties, as a result many PMI are required to carry out work that is identical to the 4Ds, namely Dirdy (dirty), and Gerous (dangerous), Demand (demand), and Death (death) which usually occurs in a closed (domestic) work environment. Factors that violate the law against TKI who are abroad are caused by, among other things, the structure of the labor market in Indonesia.